Kajian Formulasi dan Karakterisasi Self-nanoemulsifying Drug Delivery System (SNEDDS) sebagai Penghantar Agen Antihiperlipidemia Oral - Dyah Ayu Nurismawati; Sani Ega Priani (UPT Publikasi Ilmiah Unisba, 2021)
Abstract. Hyperlipidemia is one of the risk factors of various cardiovascular diseases. Several oral antihyperlipidemic agents are known to belong to BCS class II where the active substance has low solubility in water so that it has the impact of low production of dissolution profile and pharmacological effects. One of the delivery systems that can improve the solubility of hydrophobic pharmaceutical active substances is SNEDDS (Self-nanoemulsifying Drug Delivery System). This literature study aims to determine the SNEDDS formulation and its characteristics. The method used is the systematic literature review which consists of a series of stages including designing, searching, retrieving, selecting, and determining articles based on inclusion criteria. Several active substances that formulated into SNEDDS consisted of rosuvastatin, atorvastatin, ezetimibe, gemfibrozil, and perillaldehyde. Different compositions in each SNEDDS formula provide a various characteristic (particle size, polydispersity index, zeta potential value, and emulsification time) of the resulting nanoemulsion. The best formula is ezetimibe-loaded SNEDDS with a particle size of 54,07 nm; zeta potential of -38,76 mV; and emulsification time of 0,6 second. Abstrak. Hiperlipidemia merupakan salah satu faktor resiko penyebab berbagai penyakit kardiovaskular. Diketahui beberapa agen antihiperlipidemia oral termasuk ke dalam BCS kelas II dimana zat aktif memiliki kelarutan yang rendah dalam air sehingga berdampak pada rendahnya profil disolusi dan efek farmakologi yang dihasilkan. Self-nanoemulsifying Drug Delivery System (SNEDDS) merupakan salah satu sistem penghantaran yang mampu memperbaiki kelarutan zat aktif farmasi hidrofobik. Studi literatur ini bertujuan untuk mengetahui formulasi SNEDDS dan karakteristiknya. Metode yang digunakan yaitu systematic literature review yang terdiri atas serangkaian tahap meliputi perancangan, pencarian, pengambilan, seleksi, dan penentuan artikel berdasarkan kriteria inklusi. Beberapa senyawa aktif yang diformulasikan menjadi SNEDDS terdiri dari rosuvastatin, atorvastatin, ezetimib, gemfibrozil, dan perillaldehyde. Komponen bahan yang berbeda dalam setiap formula menghasilkan variasi karakteristik (ukuran partikel, indeks polidispersitas, nilai zeta potensial, dan waktu emulsifikasi) nanoemulsi yang dihasilkan. Formula yang paling memenuhi kriteria adalah SNEDDS ezetimibe dengan ukuran partikel 54,07 nm; nilai zeta potensial -38,76 mV; dan waktu emulsifikasi 0,6 detik.